2021
DOI: 10.1073/pnas.2114242118
|View full text |Cite
|
Sign up to set email alerts
|

Double peroxidase and histone acetyltransferase AgTip60 maintain innate immune memory in primed mosquitoes

Abstract: Immune priming in Anopheles gambiae is mediated by the systemic release of a hemocyte differentiation factor (HDF), a complex of lipoxin A4 bound to Evokin, a lipid carrier. HDF increases the proportion of circulating granulocytes and enhances mosquito cellular immunity. Here, we show that Evokin is present in hemocytes and fat-body cells, and messenger RNA (mRNA) expression increases significantly after immune priming. The double peroxidase (DBLOX) enzyme, present in insects but not in vertebrates, is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…We suggest that oral immune priming in T. castaneum may depend on the interplay of host immune factors with members of the resident microbiome and the pathogen itself. Any direct role of the gut microbiota for an unspecific immune priming effect via hemolymph factors as observed in Anopheles gambiae ( Rodrigues et al, 2010 ; Gomes et al, 2021 ) is unlikely in our system because it could not explain the observed bacterial-strain specificity of the oral priming response ( Futo et al, 2017 ). A study in Drosophila revealed that antiviral resistance is achieved by a two-signal system: microbiota-dependent priming and virus-dependent sensing ( Sansone et al, 2015 ).…”
Section: Discussionmentioning
confidence: 94%
“…We suggest that oral immune priming in T. castaneum may depend on the interplay of host immune factors with members of the resident microbiome and the pathogen itself. Any direct role of the gut microbiota for an unspecific immune priming effect via hemolymph factors as observed in Anopheles gambiae ( Rodrigues et al, 2010 ; Gomes et al, 2021 ) is unlikely in our system because it could not explain the observed bacterial-strain specificity of the oral priming response ( Futo et al, 2017 ). A study in Drosophila revealed that antiviral resistance is achieved by a two-signal system: microbiota-dependent priming and virus-dependent sensing ( Sansone et al, 2015 ).…”
Section: Discussionmentioning
confidence: 94%
“…HDF is a complex of lipoxin A4 (LXA4) bound to Evokin, a lipid carrier of the lipocalin family [ 39 ]. More recently, LXA4 synthesis was shown to require the activity of a third HPX—double-peroxidase (DBLOX)—produced by oenocytes, a subpopulation of fat body cells that proliferates in primed mosquitoes ( Fig 1A ) [ 40 ]. DBLOX and Evokin expression remain high after infection.…”
Section: Plasmodium Infection Primes the Anopheles...mentioning
confidence: 99%
“…The observation that a single systemic injection of PGE2 also triggers a long-lasting increase in DBLOX expression, and HDF release, suggested that epigenetic factors could be important mediators of immune priming. A functional screening in which all mosquito histone acetyltransferase (HATs) were silenced revealed that the HAT Tip60 is, indeed, essential for priming [ 40 ].…”
Section: Plasmodium Infection Primes the Anopheles...mentioning
confidence: 99%
See 1 more Smart Citation
“…The A. gambiae Sua5.1 hemocyte-like cell line 7 , 11 has been extensively used in studies on mosquito immunity 12 19 . It was also used as an in vitro tool, for example, to test the functionality of the bi-partite GAL4-UAS expression system 20 , to explore the activity of putative constitutive promoters of the A. gambiae genes 21 , 22 , or to study fundamental developmental biology of A. gambiae 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%